Air-for-water substitution in characterizing lake heatwaves in the middle and lower reaches of the Yangtze River Basin - Zihan Zhu; Wei Wang; Heng Lyu; Bo Wang; Zhiwen Wen; Qiuxiang Jin (Journal of Hydrology: Regional Studies, 2025)
Study region: This study focuses on seventeen lakes with surface area larger than 100 km2 located in the middle and lower reaches of the Yangtze River Basin, China. Study focus: This study compares the spatiotemporal differences between lake heatwave and atmospheric heatwave metrics and elucidates the intensity differences between two heatwaves across seventeen lakes in the middle and lower reaches of the Yangtze River Basin. New hydrological insights for the region: This study demonstrated that air-for-water substitution is invalid in characterizing lake heatwaves in this region. Compared to atmospheric heatwaves, lake heatwaves in the study region are characterized by higher frequency, lower intensity, and longer duration. Significantly more frequent and longer-lasting lake heatwaves are observed in the middle and lower reaches of the Yangtze River. At the interannual timescale, lake heatwaves are increasing faster than atmospheric ones by 0.8 d per decade in total annual duration and 1.2 times as fast in frequency, but more slowly by 0.3 K per decade in average intensity. But the difference in long-term change rates between two heatwaves exhibits no discernible spatial pattern. Although air temperature (4.41 K, 94.23 % of the total) is the largest contributor to the average intensity of lake heatwaves, other meteorological variables collectively modulate lake heatwave intensity and cannot be neglected.